Code Mixing and Code Switching in Maudy Ayunda’s YouTube Channel - Dewi Purnama Sari; Maya Putri Hartanti (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
In the current era of globalization many people ability use more than one language, this phenomenon in sociolinguistics studies is called code mixing and code switching. In Indonesia there are many artists or actors who use code mixing and code switching in everyday their utterances. One of Indonesian artist who uses code mixing and code switching is Maudy Ayunda. In her YouTube video entitled Thoughts on Adulting, Thoughts on Gap Year, Thoughts on how English changed my life, Thoughts on Failures + GRWM!, she uses code mixing and code switching in Indonesian and English in her utterances. This aim of this research is finding the types of code mixing and code switching and the factor of using code mixing and code switching also finding any interference in Maudy Ayunda's utterances as the impact of code mixing and code switching usage. This research used descriptive qualitative research and the data were analyzed using the theory of Hoffmann. The result of this research indicated that there 176 data points from four video. There are three types of code mixing in Maudy Ayunda’s of four video YouTube channel which are accured including : Intra sentential mixing occurs 109 times, intra lexical 11 times, and involving change pronunciation occurs 14 times. Further, there are 3 types of code switching which are used by Maudy Ayunda such as: intra sentential switching occurs 68 times , inter sentential switching occurs 14 times and emblematic switching occurs 6 times. In each of the video intra sentential mixing is the most dominant used in Maudy's utterances.